In Pursuit of the Determinants of Users’ Views on and Usage Practices Associated with the use of Virtual Systems in an Emerging Economy - Majharul Talukder (Australasian Accounting, Business and Finance Journal, 2019)
While there has been extensive research on the adoption of an innovation in general, research on adoption of a specific innovation such as virtual systems in an emerging economy is relatively scarce. This research addresses this lacuna in the extant literature by empirically investigating the potential drivers impacting on the practice of virtual systems at the individual level in an emerging economy, Bangladesh. The data for the study comprises responses obtained through a cross-sectional survey of individuals using a structured instrument. Data were analyzed using correlation and multiple regression analysis. Findings suggest that a personal initiative is one of the strongest predictors of virtual device adoption, followed by self-fulfillment with innovation and peer pressure. Surprisingly benefits and social pressure did not show any significant relationship with usage. The implications of these findings are highlighted in the paper along with the limits and future potential of research in this area.
Keywords: Benefits; personal initiatives; self-esteem; self-fulfillment; peer pressure; social pressure; virtual devices; smart phone; smartphone